Market themes and variations - Kahn, Michael N. (FT Press Delivers elements, 2011)
"This Element is an excerpt from Technical Analysis Plain and Simple: Charting the Markets in Your Language (ISBN: 9780137042012), by Michael N. Kahn. Beyond mere "pattern recognition": how to interpret the subtle and not-so-subtle variations that appear in real-world charts"--Resource description page.